Math, asked by Raghava9302, 1 year ago

Write the quadratic polynomial whose zeros are 1/α and 1/β

Answers

Answered by TrickYwriTer
14

Step-by-step explanation:

Given -

  • Zeroes of the polynomial is 1/α and 1/β

To Find -

  • A quadratic polynomial

Method 1 :-

As we know that :-

  • α + β = -b/a

→ 1/α + 1/β = -b/a

→ β + α/αβ = -b/a ....... (i)

And

  • αβ = c/a

→ 1/α × 1/β = c/a

→ 1/αβ = c/a ...... (ii)

Now, From (i) and (ii), we get :

a = αβ

b = -(α + β)

c = 1

Now,

As we know that :-

For quadratic polynomial :

  • ax² + bx + c

→ αβx² - (α + β)x + 1

→ αβx² - (α + β)x + 1

The quadratic polynomial is αβx² - (α + β)x + 1

Method 2 :-

As we know that :-

For a quadratic polynomial :

x² - (sum of zeroes)x + (product of zeroes)

→ x² - [(α + β)x/αβ] + 1/αβ = 0

→ αβx² - (α + β)x + 1/αβ = 0

→ αβx² - (α + β)x + 1 = 0

Hence,

The quadratic polynomial is αβx² - (α + β)x + 1

Answered by silentlover45
9

  \huge \mathfrak{Answer:-}

\large\underline\mathrm{The \: quadratic \: polynomial \: is βαx² \:  -(α \: + \: β)x \: + \: 1.}

\large\underline\mathrm{Given:-}

  • zeros are 1/α and 1/β

\large\underline\mathrm{To \: find}

  • A quadratic polynomial.

\large\underline\mathrm{Solution}

  • 1/α + 1/β = -b/a

\implies 1/α + 1/β = -b/a

\implies β + α/βα = -b/a. ...(1)

\large\underline\mathrm{and}

  • βα = c/a

\implies 1/α × 1/β = c/a

\implies 1/βα = c/a. ....(2)

\large\underline\mathrm{Now,}

\large\underline\mathrm{Eq. \: (1) \: \: and \: Eq. \: (2), \: we \: get;}

\implies a = βα

\implies b = -(α + β)

\implies c = 1

\large\underline\mathrm{Thus,}

\large\underline\mathrm{using \: the \: formula \: in \: quadratic \: polynomial \: ;}

\implies ax² + bx - c

\implies βαx² -(α + β)x + 1

\large\underline\mathrm{The \: \: quadratic \: polynomial;}

\implies αβx² - (α + β)x + 1

\large\underline\mathrm{Thus,}

\large\underline\mathrm{for \: the \: quadratic \: polynomial.}

\implies x² - (sum of zeroes)x + (products of zeroes)

\implies x² - [(α + β)x/αβ] + 1/βα = 0

\implies βαx² -(α + β)x + 1/βα

\implies βαx² -(α + β)x + 1 = 0

\large\underline\mathrm{hence,}

\large\underline\mathrm{The \: quadratic \: polynomial \: is βαx² \:  -(α \: + \: β)x \: + \: 1.}

\large\underline\mathrm{Hope \: it \: helps \: you \: plz \: mark \: me \: brainlist}

Similar questions